Mortality of ethnic minority groups in the UK: a systematic review protocol. Issue 6 (28th June 2020) - Stanaway, Fiona; Noguchi, Naomi; Mathieu, Erin; Khalatbari-Soltani, Saman; Bhopal, Raj
Abstract : Introduction: Growing ethnic diversity in the UK has made it increasingly important to determine the presence of ethnic health inequalities. There has been no systematic review that has drawn together research on ethnic differences in mortality in the UK. Methods: All types of observational studies that compare all-cause mortality between major ethnic groups and the white majority population in the UK will be included. We will search Medline (OvidSP), Embase (OvidSP), Scopus and Web of Science and search the grey literature through conference proceedings and online thesis registries. Searches will be carried out from inception to 2 August 2019 with no language or other restrictions. Database searches will be repeated prior to publication to identify new articles published since the initial search. We will conduct forward and backward citation tracking of identified references and consult with experts in the field to identify further publications and ongoing or unpublished studies. Two reviewers will independently screen studies and extract data. Two reviewers will independently assess the quality of included studies using the Newcastle-Ottawa Scale. If at least two studies are located for each ethnic group and studies are sufficiently homogeneous, we will conduct a meta-analysis. If insufficient studies are located or if there is high heterogeneity we will produce a narrative summary of results. Ethics and dissemination: As no primary data will be collected, formal ethical approval is not required. The findings of this review will be disseminated through publication in peer reviewed journals and conference presentations. PROSPERO registration number: CRD42019146143.